O estatuto variável do imperativo de 2ª pessoa do singular em missivas mineiras: um estudo sociolinguístico de cunho histórico (séculos XIX e XX) - Luiz Fernando de Carvalho (2020)
This research investigates the variable status of the second person singular – Imperative Mood – in letters written by illustrious writers from the state of Minas Gerais, Brazil, from the nineteenth and twentieth century in order to verify the distribution of imperative constructions in terms of linguistic and extralinguistic factors. This analysis, guided by the methodological principles of Historical Sociolinguistics (ROMAINE, 1982; CONDE SILVESTRE, 2007; HERNÁNDEZ-CAMPOY et CONDE SILVESTRE, 2014) inspired by the postulates of Variationist Sociolinguistics (WEINREICH, LABOV, HERZOG, 1968; LABOV 1994, 2001), seeks to reconstitute the variable phenomenon, addressed in studies under the bias of diachrony (FARACO, 1982; PAREDES SILVA et al., 2000; RUMEU, 2016, 2019; DINIZ, 2018), in comparison with research in the scope of synchrony (SCHERRE et al., 1998, 2000, 2014; SCHERRE, 2003, 2004, 2007, 2012; CARDOSO, 2009; EVANGELISTA, 2010; CARDOSO, 2012). This paper understands that the insertion of você in the pronominal framework of Brazilian Portuguese (LOPES, 2007; LOPES et al., 2011) has reflected on the imperative forms associated with the indicative (deixa/recebe/abre/dá/diz/vai) and the subjunctive (deixa/recebe/abre/dá/diz/vai), whose realization, contrary to the normative bias, does not necessarily occur in complementary distribution with the second-person singular subject pronoun options of Brazilian Portuguese (tu and você). This scenario enabled the emergence of the abrasileirado imperative, an imperative construction with the form associated with the indicator in the discursive context of você as the subject, diatopically distributed in Brazil in sentences such as Vem pra Caixa você também!. In this sense, considering that the imperative variable expression is motivated by linguistic and extralinguistic factors, it aims to understand the manifestation of the phenomenon, in search of traces of the abrasileirado imperative, in the nineteenth and twentieth century letters (loving, friendship and family) signed by proven illustrious writers, legitimated representatives of the standard norm in Minas Gerais. In general, the results of this research show a predominance of imperative forms associated with the subjunctive over imperative forms related to the indicative, given the productivity of the letters using você as a subject, which influenced the writing in Minas Gerais, once the writers, holders of a high level education, were influenced by the standard norm. In any case, even though the imperative associated with the subjunctive has prevailed, in addition to the imperative's variable status being sensitive to the linguistic factors subject of the letters, formal parallelism, phonic parallelism, polarity of structure, and the extralinguistic factor of the subgenre personal letter, traces of the abrasileirado imperative have been found in letters with você as the subject as well as in mixed letters, with você and tu in the subject position. These results focused on the study of the imperative contribute to the understanding of the phenomena of variation and change which demonstrate the heterogeneous character of natural languages.